A Jehovah’s Witness with Acute Myeloid Leukemia Successfully Treated with an Epigenetic Drug, Azacitidine: A Clue for Development of Anti-AML Therapy Requiring Minimum Blood Transfusions - Yumi Yamamoto; Akihito Kawashima; Eri Kashiwagi; Kiyoyuki Ogata (Case Reports in Hematology)
Therapy for acute leukemia in Jehovah’s Witnesses patients is very challenging because of their refusal to accept blood transfusions, a fundamental supportive therapy for this disease. These patients are often denied treatment for fear of treatment-related death. We present the first Jehovah’s Witness patient with acute myeloid leukemia (AML) treated successfully with azacitidine. After achieving complete remission (CR) with one course of azacitidine therapy, the patient received conventional postremission chemotherapy and remained in CR. In the case of patients who accept blood transfusions, there are reports indicating the treatment of AML patients with azacitidine. In these reports, azacitidine therapy was less toxic, including hematoxicity, compared with conventional chemotherapy. The CR rate in azacitidine-treated patients was inadequate; however, some characteristics could be useful in predicting azacitidine responders. The present case is useful for treating Jehovah’s Witnesses patients with AML and provides a clue for anti-AML therapy requiring minimum blood transfusions.